Analisis Yuridis terhadap Kedudukan Ahli Waris Pengganti dalam Putusan PA Jombang No. 362/Pdt.P/2024/PA.Jbg - Ramadhani, Muhammad Hidayatulloh; Masrokhin Masrokhin (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Abstrak. This research departs from the variations among the provisions for alternative heirs in classical Islamic inheritance regulation and practices in Indonesia, mainly through decision variety 362/Pdt.P/2024/PA. Jbg with the aid of the Jombang spiritual courtroom. The point of interest of this observe is on how the idea of alternative heirs is implemented in that decision, as well as its impact on the Islamic inheritance law machine in Indonesia. The method used is juridical-normative with a case observe method, counting on information from decision files, interviews with judges, as well as research of classical and present day literature. The results display that the choose increased the that means of Article 185 of the KHI via ijtihad, including nephews as substitute heirs. The attention is based totally at the concepts of justice and family values. This selection contributes to the renewal of Islamic inheritance law, making it greater inclusive and contextual with the local Indonesian subculture. Keywords: Replacement Heir; Islamic Inheritance law; Spiritual Courtroom Decision. Abstrak. Penelitian ini berangkat asal adanya disparitas antara ketentuan ahli waris pengganti pada aturan kewarisan Islam klasik serta praktik di Indonesia, khususnya melalui Putusan nomor 362/Pdt.P/2024/PA.Jbg oleh Pengadilan Agama Jombang. Fokus kajian ini merupakan bagaimana penerapan konsep ahli waris pengganti dalam putusan tadi, serta dampaknya terhadap sistem hukum kewarisan Islam di Indonesia. Pendekatan yang digunakan bersifat yuridis normatif dengan metode studi masalah, mengandalkan data berasal dokumen putusan, wawancara menggunakan hakim, serta kajian literatur klasik serta pada masa ini. Hasilnya menunjukkan bahwa hakim memperluas makna Pasal 185 KHI secara ijtihadi, termasuk keponakan menjadi pakar waris pengganti. Pertimbangan didasarkan pada asas keadilan serta nilai kekeluargaan. Putusan ini berkontribusi terhadap pembaruan aturan kewarisan Islam yang lebih inklusif dan kontekstual menggunakan budaya lokal Indonesia. Kata Kunci: Ahli Waris Pengganti; Hukum Kewarisan Islam; Putusan Pengadilan Agama.